Development and Validation of a Rapid and Sensitive LC-MS/MS Method for the Pharmacokinetic Study of Osimertinib in Rats. (22nd November 2019) - Xiong, Shan; Deng, Zhipeng; Sun, Peilu; Mu, Yanling; Xue, Mingxing
Abstract: Osimertinib is a new-generation epidermal growth factor inhibitor for the treatment of non-small cell lung cancer. In the present study, a rapid and sensitive LC with tandem MS method was developed and validated for the determination of osimertinib in rat plasma. Chromatographic separation was carried out on a C18 column using acetonitrile and water containing 0.1% formic acid. The assay was validated over a concentration range of 1.0–1000 ng/mL for osimertinib, with a lower LOQ of 1.0 ng/mL. The intra- and interday accuracy values for osimertinib ranged from 92.66 to 101.50% and from 97.08 to 99.15%, respectively, and the intra- and interday precision values for osimertinib ranged from 6.25 to 10.34% and from 3.43 to 10.44%, respectively. The method was successfully applied in a pharmacokinetic study of osimertinib after oral administration of osimertinib (4.5 mg/kg) to rats.